RELEVANSI TASAWUF DI ERA MODERN - Sirajuddin Zar (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2019)
Islam is not just a legalistic-formalistic side, but it also has an esoteric dimension. Sufism is an important element in Islam which is more focused on the esoteric aspects of Islam. This inward aspect of Islam is more influenced by feelings (zauq) and is personal and in re-vealing its teachings often uses figurative words (matsal) and symbols (ramz). The aim of the Sufi is toget as close as possible to God, so that he can see God with the eyes of the heart, even his spirit can be united with the spirit of God. Islamic mysticism does not deny science, even Islamic mysticism contributes a lot of ideas in the fields of philosophy, literature, music, dance, psychology, and modern science. The problem of alienation is a psychological problem. Humans play a role as the cause of the emergence of alienation and at the same time as a victim who must bear the consequences. In the context of Islamic teachings, to overcome the alienation of the human soul and free from the pain of alienation, it must instead make God the ultimate goal, the Supreme Being and the Absolute. All relative and relative existence is meaning-less before the existence of the absolute.